ASPEK PEMBENTUK IDENTITAS PERKOTAAN TEPI LAUT: STUDI KASUS KAWASAN MATTIROTASI KOTA PAREPARE - Muhammad Uliah Shafar; Muhammad Rusdin Jumurdin; Ni'mah Natsir (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze the identity of public spaces in waterfront areas undergoing rapid development, which raises important questions regarding their evolving identity. The findings from this research are expected to contribute to the design and planning of more effective and memorable public spaces in the future. As part of the effort to understand the identity of these spaces, the study explores the dynamic interaction between physical form, activities, and meaning in shaping the unique character of waterfront public spaces.The research employs a qualitative descriptive approach and focuses on a single case study to examine phenomena related to physical form, activity, and meaning. Data collection was carried out through direct observation, followed by a thorough analysis based on literature studies. The case study area selected for this research was the Mattirotasi seafront. The results show that the aspects of this public space do not sufficiently maintain its identity. This is attributed to factors such as limited accessibility, low legibility, environmental degradation, and the limited connectivity between public spaces. Consequently, the relationship between the space and its surrounding environment has been disrupted. This preliminary research offers a significant contribution by filling a gap in the literature on the identity of public spaces in waterfront areas, providing practical implications for urban designers and policymakers in developing effective strategies for the management and design of waterfront public spaces.